LEGAL SETTLEMENT OF TAX AVOIDANCE PRACTICES BY FOREIGN WORKERS WORKING IN INDONESIA - Yoanes Daru Weda - (Jurnal Paradigma Hukum Pembangunan, 2026)
The increasing presence of foreign workers in Indonesia as a result of globalization has created challenges in the imposition of Income Tax, particularly related to tax avoidance practices. Although the taxation of foreign workers has been normatively regulated under Indonesian tax laws, in practice there remain legal loopholes and weak supervision that allow tax avoidance to occur. This study aims to analyze the legal framework governing Income Tax on foreign workers, identify common forms of tax avoidance, and examine the available legal mechanisms for their resolution. This research employs a normative legal research method using statutory and comparative law approaches. The findings indicate that tax avoidance by foreign workers commonly occurs through dual payroll schemes, manipulation of reported income, and non-compliance in reporting foreign assets. Furthermore, enforcement through administrative and criminal sanctions has not yet been fully effective. A comparison with Malaysia shows that preventive administrative measures are more effective in reducing tax avoidance by foreign workers.